C7 multi-messenger astronomy of GW sources - Branchesi, M.; Woan, G.; Astone, P.; Bartos, I.; Colla, A.; Covino, S.; Drago, M.; Fan, X.; Frasca, S.; Hanna, C.; Haskell, B.; Hazboun, J.; et al. (Springer New York LLC, 2014)
We summarise the parallel session C7 Multi-Messenger Astronomy of GW Sources in the GR20 Amaldi 10 Conference. The talks in this session covered a wide range of topics in multi-messenger astronomy.